Sex Similarities/Differences in Trajectories of Delinquency among urban Chicago Youth: The Role of Delinquent Peers - Jennings, Wesley G. (American journal of criminal justice, 2010)
A growing body of literature has recently emerged examining sex-specific pathways of offending. Yet, despite significant gains, this area of research is still rather underexplored. With a particular focus on the role of delinquent peers, this current study investigates the sex similarities/differences in offending trajectories among a large sample of urban Chicago male and female youth ( n = 3,038) from 6th through 8th grade (e.g., ages 12–14). The results suggest that the pathways of offending appear to be more similar than different across sex, and that associating with delinquent peers is significantly related to baseline delinquency. Furthermore, delinquent peers significantly distinguished the moderate and high-rate trajectory groups from the non-delinquents for both males and females, yet once estimated in a more fully specified model, the role of delinquent peers appeared to be indirect (operating through its effect on baseline delinquency). Study limitations and implications for theory and policy are also discussed.